2021
DOI: 10.3390/polym13132104
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hybrid Nanofibers from Biopolymers and Poly (Vinyl Alcohol)/Poly (ε-Caprolactone) for Wound Dressing Applications

Abstract: The management of chronic wounds is challenging. The factors that impede wound healing include malnutrition, diseases (such as diabetes, cancer), and bacterial infection. Most of the presently utilized wound dressing materials suffer from severe limitations, including poor antibacterial and mechanical properties. Wound dressings formulated from the combination of biopolymers and synthetic polymers (i.e., poly (vinyl alcohol) or poly (ε-caprolactone) display interesting properties, including good biocompatibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 154 publications
(164 reference statements)
0
35
0
Order By: Relevance
“…The initial phase of the study focused on developing NF mats of different weight percentages and was optimized by screening against microbes for potential antimicrobial activity. The synthesized fibers were characterized using SEM and FTIR and the tensile strength of B-PEI NF indicates a good enhancement in the mechanical property after the addition of PEI with PVA, which matches the typical range of mechanical strength suitable for wound dressing applications. , …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The initial phase of the study focused on developing NF mats of different weight percentages and was optimized by screening against microbes for potential antimicrobial activity. The synthesized fibers were characterized using SEM and FTIR and the tensile strength of B-PEI NF indicates a good enhancement in the mechanical property after the addition of PEI with PVA, which matches the typical range of mechanical strength suitable for wound dressing applications. , …”
Section: Discussionmentioning
confidence: 76%
“…The synthesized fibers were characterized using SEM and FTIR and the tensile strength of B-PEI NF indicates a good enhancement in the mechanical property after the addition of PEI with PVA, which matches the typical range of mechanical strength suitable for wound dressing applications. 59,60 Assays have shown that B-PEI increases the permeability of the cell membranes. 61 Depolarization of the membrane potential is also considered a cell disruption mechanism of B-PEI.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Natural-based polymeric wound dressing materials are usually cross-linked with synthetic polymers to enhance their mechanical performance [14]. The synthetic polymers that can be cross-linked with natural polymers for wound dressing formulations include poly(vinyl alcohol) (PVA), poly(lactic-co-glycolic acid) (PLGA), polylactide (PLA), polyglycolic acid (PGA), polyurethanes (PUs), poly(ethylene oxide) (PEO)/poly(ethylene glycol) (PEG), poly(hydroxyethyl methacrylate) (PHEMA), and poly(vinyl pyrrolidone) (PVP) [15]. The cross-linked dressings can also exhibit poor biological activities and weak wound healing properties, making them inappropriate for managing diabetic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning can form nanofibers that are much smaller than the size of cells and can also form porous structures, which are good for stimulating the growth of cells through environmental cues within the body. In 2002, Li et al proposed the advantages of electrostatic nanofiber technology for use at the level of tissue engineering [ 13 ], Yoshimoto et al further confirmed the great potential of electrostatic nanofibers as bone tissue engineering scaffolds [ 14 ], Alven and Aderibigbe reviewed the PVA/PCL hybrid nanofiber for wound dressing application [ 15 ].…”
Section: Introductionmentioning
confidence: 99%